Risk detection of osteoporosis with panoramic radiograph using mental index in 30-60 years old patients (an overview in Ulin Hospital Banjarmasin) - Nadia Chairina; Didit Aspriyanto; Norlaila Sarifah (Ikatan Radiologi Kedokteran Gigi Indonesia, 2022)
Objectives: This research is aimed to determine the detection of osteoporosis risk with a panoramic radiograph using mental index in 30-60 years old patients in Ulin Hospital Banjarmasin. Materials and Methods: This research is using descriptive study with a cross-sectional study design. This research sample using secondary data from 30-60 years old patients who took panoramic radiographs in Radiology Installation of Ulin Hospital Banjarmasin from January 2018 – December 2021. Results: The result showed that the age group at risk of osteoporosis was the age group 56-60 years old (right jaw 3.44 ± 0.70 and left jaw 3.33 ± 0.32), gender at risk of osteoporosis is men (right jaw 3.44 ± 0.52 and left jaw 3.37 ± 0.44) and the mean value of the mandibular cortex width in the group at risk for osteoporosis was 2.91 ± 0.21. Conclusion: The age group at risk of osteoporosis is the age of 56-60 years old and the gender at risk of osteoporosis is men. Mental index can be used as a tool for measuring the mandibular cortex width on panoramic radiographs to diagnose the risk of osteoporosis.